PARK Genes Link Mitochondrial Dysfunction and Alpha-Synuclein Pathology in Sporadic Parkinson’s Disease - Li, Wen; Fu, YuHong; Halliday, Glenda M.; Sue, Carolyn M. (Frontiers in Cell and Developmental Biology, 2021)
Parkinson’s disease (PD) is an age-related neurodegenerative disorder affecting millions of people worldwide. The disease is characterised by the progressive loss of dopaminergic neurons and spread of Lewy pathology (alpha-synuclein aggregates) in the brain but the pathogenesis remains elusive. PD presents substantial clinical and genetic variability. Although its complex aetiology and pathogenesis has hampered the breakthrough in targeting disease modification, recent genetic tools advanced our approaches. As such, mitochondrial dysfunction has been identified as a major pathogenic hub for both familial and sporadic PD. In this review, we summarise the effect of mutations in 11 PARK genes (SNCA, PRKN, PINK1, DJ-1, LRRK2, ATP13A2, PLA2G6, FBXO6, VPS35, CHCHD2, and VPS13C) on mitochondrial function as well as their relevance in the formation of Lewy pathology. Overall, these genes play key roles in mitochondrial homeostatic control (biogenesis and mitophagy) and functions (e.g., energy production and oxidative stress), which may crosstalk with autophagy pathway, induce proinflammatory immune response, and increased oxidative stress that facilitate the aggregation of alpha-synuclein. Thus, rectifying mitochondrial dysregulation represents a promising therapeutic approach for neuroprotection in PD.